Seoulmates - Lee, Susan, (Novelist) (2022)
Hannah Cho had the next year all planned out--the perfect summer with her boyfriend, Nate, and then a fun senior year with their friends. But then Nate does what everyone else in Hannah's life seems to do--he leaves her, claiming they have nothing in common. He and all her friends are newly obsessed with K-pop and K-dramas, and Hannah is not. After years of trying to embrace the American part and shunning the Korean side of her Korean American identity to fit in, Hannah finds that's exactly what now has her on the outs. But someone who does know K-dramas--so well that he's actually starring in one--is Jacob Kim, Hannah's former best friend, whom she hasn't seen in years. He's desperate for a break from the fame, so a family trip back to San Diego might be just what he need that is, if he and Hannah can figure out what went wrong when they last parted and navigate the new feelings developing between them. --
Grades 7-9 ; ages 13-17 years.
Keywords: Korean American teenagers -- Juvenile fiction; Actresses -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; K-pop (Subculture) -- Juvenile fiction; Young adult fiction; Actors -- Fiction; Actresses -- Fiction; Korean American teenagers -- Fiction; San Diego (Calif.) -- Juvenile fiction; San Diego (Calif.) -- Fiction; Young adult fiction; Romance fiction; Bildungsromans; Novels